Single-Dose Mucosal Immunotherapy With Chimpanzee Adenovirus-Based Vaccine Accelerates Tuberculosis Disease Control and Limits Its Rebound After Antibiotic Cessation. (13th June 2019) - Afkhami, Sam; Lai, Rocky; D'agostino, Michael R; Vaseghi-Shanjani, Maryam; Zganiacz, Anna; Yao, Yushi; Jeyanathan, Mangalakumari; Xing, Zhou
Abstract: Background: The development of strategies to accelerate disease resolution and shorten antibiotic therapy is imperative in curbing the global tuberculosis epidemic. Therapeutic application of novel vaccines adjunct to antibiotics represents such a strategy. Methods: By using a murine model of pulmonary tuberculosis (TB), we have investigated whether a single respiratory mucosal therapeutic delivery of a novel chimpanzee adenovirus-vectored vaccine expressing Ag85A (AdCh68Ag85A) accelerates TB disease control in conjunction with antibiotics and restricts pulmonary disease rebound after premature (nonsterilizing) antibiotic cessation. Results: We find that immunotherapy via the respiratory mucosal, but not parenteral, route significantly accelerates pulmonary mycobacterial clearance, limits lung pathology, and restricts disease rebound after premature antibiotic cessation. We further show that vaccine-activated antigen-specific T cells, particularly CD8 T cells, in the lung play an important role in immunotherapeutic effects. Conclusions: Our results indicate that a single-dose respiratory mucosal immunotherapy with AdCh68Ag85A adjunct to antibiotic therapy has the potential to significantly accelerate disease control and shorten the duration of conventional treatment. Our study provides the proof of principle to support therapeutic applications of viral-vectored vaccines via the respiratory route. Abstract : Using a murine model of pulmonary TB, a single respiratory mucosal delivery of chimpanzee adenoviral-based TB vaccine in conjunction with antibiotic therapy markedly improved disease treatment and restricted its relapse after antibiotic cessation.